The Effect Of Chest Percussion On The Reduction Of Additional Breath Sounds In Pneumonia Patients In The Bougenville Room Of Rumah Sakit dr. Haryoto Lumajang - Wahyu Widyanuari, Dwi Shanti; Hartono, Dodik; Abidin, Zainal (NHM PRESS, 2024)
Pneumonia is an acute inflammation of lung tissue caused by microorganisms, symptoms that appear such as increased temperature and can be accompanied by seizures, restlessness, cyanosis, shortness of breath, and productive coughing, so that proper treatment is needed to remove sputum that accumulates in the airways, one of which is chest physiotherapy with the Chest Percussion method. The purpose of this study is to determine the effect of Chest Percussion on the decrease in additional breath sounds in pneumonia patients in the bougenville room of Rumah Sakit dr. Haryoto Lumajang. The design of this study was a pre-experimental study using a one-group pretest-posttest approach using standard operating procedures on chest percussion and observation sheets for additional breathing sounds. The statistical test used was the wilcoxon test, with a research sample of 31 respondents taken by the accidental sampling method from July 31 until August 30, 2024. The results in this study showed that of the 20 (64.5%) respondents with missing ronkhi when coughing/inhaling before the Chest Percussion action, there were 18 (90%) respondents who at the time after the procedure changed to sound smooth ronkhi and the remaining 2 (10%) did not experience any change. Meanwhile, in 11 (35.5%) respondents who at the time before the Chest Percussion action heard a smooth ronkhi sound, 11 (100%) of the respondents after receiving the action changed to clear. The results of the Wilcoxon statistical test obtained a p-value of 0.000 (p < 0.05) which means that there is a significant influence between Chest Percussion on additional decrease of breathing sounds in pneumonia patients. The results of this study can be concluded that Chest Percussion can reduce sputum in pneumonia patients, with reduced sputum the sound of the ronkhi in pneumonia patients can be reduced. It can be recommended for hospitals that Chest Percussion is a guideline in treating pneumonia with additional sounds.